Analysis of Financial Planning and The Factors that Influence It: Student Case Study - Alamsyah, Akla Rizka; Ulya, Zikriatul; Hisan, Khairatun (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2023)
This research aims to determine the effect of financial literacy, financial behavior and self-control on student financial planning. This research is a quantitative study of 213 respondents using simple random sampling technique with the requirement that students have taken financial planning courses. Data analysis using SmartPLS with two model tests. The results obtained are that financial literacy, financial behavior and self-control have a positive and significant effect on financial planning partially. The findings also show that there is an indirect effect through self-control that financial literacy has a positive but not significant effect, but has a positive and significant effect on the relationship between financial behavior to financial planning. These results indicate that financial management knowledge will be much more useful if it is practiced in everyday life to achieve planned financial goals. For this reason, it is important for the world of education not only to teach financial knowledge, but also to help improve individual behavior so that they have good discipline and self-control.